Exogenous ascorbic acid is a pro-nitrant in Arabidopsis thaliana - Feigl, Gábor; Bordé, Ádám; Molnár, Árpád; Kolbert, Zsuzsanna (Acta Biologica Szegediensis, 2019)
Due to the intensified production of reactive nitrogen species (RNS) proteins can be modified by tyrosine nitration (PTN). Examination of PTN is a hot topic of plant biology, especially because the exact outcome of this modification is still pending. Both RNS and ascorbic acid (AsA) are redox-active molecules, which directly affect the redox state of cells. The possible link between RNS-dependent PTN and AsA metabolism was studied in RNS (gsnor1-3, nia1nia2) and AsA (vtc2-3) homeostasis Arabidopsis mutants. During physiological conditions, intensified PTN was detected in all mutant lines compared to the wild-type (WT); without altering nitration pattern. Moreover, the increased PTN seemed to be associated with endogenous peroxynitrite (ONOO-) levels, but it showed no tight correlation with endogenous levels of nitric-oxide (NO) or AsA. Exogenous AsA caused intensified PTN in WT, vtc2-3 and nia1nia2. In the background of increased PTN, significant NO and ONOO- accumulation was detected, indicating exogenous AsA-induced RNS burst. Interestingly, in AsA-triggered stress-situation, changes of NO levels seem to be primarily connected to the development of PTN. Our results point out for the first time that similarly to human and animal systems exogenous AsA exerts pro-nitrant effect on plant proteome.